TROMBEKTOMI MEKANIKAL PADA STROKE ISKEMIK DENGAN AWITAN KURANG DARI 6 JAM - Rakhmad Hidayat,* Affan Priyambodho,** Reyhan Eddy Yunus,*** Taufik Mesiano,* Mohammad Kurniawan,* A (NEURONA, 2017)
REPORT A CASE OF ACUTE STROKE WITHIN 3 HOUR ONSET ADMITTED TO THE EMERGENCY ROOM CIPTO MANGUNKUSUMO HOSPITAL RSCM JAKARTA THE RSCM CODE STROKE PROTOCOL WAS THEN INITIATED WHICH INCLUDED CLINICAL EXAMINATION AND NEUROIM AGING HEAD CT SCAN SHOWED NO INTRACRANIAL HEMORRHAGE